OPTIMAL PORTFOLIO ANALYSIS OF IDX-30 AND LQ-45 PORTFOLIO WITH THE CAPM METHOD OF THE INDONESIA STOCK EXCHANGE - Sarva Jayana, Nur; Pardomuan Sihombing (Dinasti Publisher, 2020)
The research objective of this portfolio is to analyze the optimal portfolio IDX-30 and its portfolio of LQ-45 with CAPM method in IDX. This research uses descriptive quantitative method. IDX-30 and LQ-45 in the Stock Exchange of the period January 2013 - December 2018 the population in the study. A Purposive sampling technique used in determining the sample. Data analysis using Microsoft Excel, from this research are, a). Based on the results of the expected return and risk of IDX-30 and LQ-45, which can be seen from an analysis of individual stocks with a CAPM portfolio. Then the chosen CAPM portfolio, because it produces a good return and minimal risk. And the highest shares of IDX-30 and LQ-45 are TLKM. with the IDX-P13 return result of 6.5809 and a risk of 7.14%. and LQ-45 P20 return of 6.5764 with a risk of 7.89%.b). Optimal portfolios formed using CAPM provide better investment returns than individual shares, because CAPM offers a higher expected return and minimum risk than individual shares. While the optimal portfolio performance of IDX-30 shares evaluated using CAPM is better than the optimal portfolio performance of LQ-45 shares.